Associations between area‐level disadvantage and DMFT among a birth cohort of Indigenous Australians. (30th January 2013) - Jamieson, LM; Do, LG; Bailie, RS; Sayers, SM; Turrell, G
Abstract Background Individual‐level factors influence DMFT, but little is known about the influence of community environment. This study examined associations between community‐level influences and DMFT among a birth cohort of Indigenous Australians aged 16–20 years. Methods Data were collected as part of Wave 3 of the Aboriginal Birth Cohort study. Fifteen community areas were established and the sample comprised 442 individuals. The outcome variable was mean DMFT with explanatory variables including diet and community disadvantage (access to services, infrastructure and communications). Data were analysed using multilevel regression modelling. Results In a null model, 13.8% of the total variance in mean DMFT was between community areas, which increased to 14.3% after adjusting for gender, age and diet. Addition of the community disadvantage variable decreased the variance between areas by 4.8%, indicating that community disadvantage explained one‐third of the area‐level variance. Residents of under‐resourced communities had significantly higher mean DMFT (β = 3.86, 95% CI 0.02, 7.70) after adjusting for gender, age and diet. Conclusions Living in under‐resourced communities was associated with greater DMFT among this disadvantaged population, indicating that policies aiming to reduce oral health‐related inequalities among vulnerable groups may benefit from taking into account factors external to individual‐level influences.